Severe Hypocalcemia in the Adolescent as the Only Manifestation of 22q11 Microdeletion Syndrome: Clinical Case - Anastasia O. Vechkasova; Natalia V. Buchinskaya; Mikhail M. Kostik (Вопросы современной педиатрии, 2023)
Background. In this article, we would like to describe the atypical clinical picture and course of 22q11 microdeletion syndrome in a patient without specific phenotypic signs and symptoms typical for this disease.Clinical case description. Male patient, 13 years old, was hospitalized for the first time with seizure and multiple spinal fractures caused by hypocalcemia. He was referred to rheumatologist and clinical geneticist after hospital stay. Differential diagnosis included not only various bones metabolic diseases, but also 22q11 deletion syndrome. Later it was confirmed via FISH test.Conclusion. This clinical case proves once again the uniqueness of every single case, as well as the importance of comprehensive approach to the diagnosis and management of such patients.